Methodology For Developing The Creative Ability Of Children Of The Pre-School Preparation Group - Gavkhar Turavoyevna Shariyeva (Euro Asian Journal Publishing, 2024)
Nowadays, the serious demands placed on children's levels of preparation for school require the development of necessary theoretical and practical measures in this regard. Conducting and developing creativity among children in the preparatory group is one of the urgent tasks today. This article talks about the method of realizing the creative abilities of children in the preparatory group and encouraging them
Keywords: creative ability; preparatory groups; preschool education system